Gonadal dysfunction in a man with Noonan syndrome from the LZTR1 variant: case report and review of literature - Orsolini, Francesca; Pignata, Luisa; Baldinotti, Fulvia; Romano, Silvia; Tonacchera, Massimo; Canale, Domenico (Frontiers in Endocrinology, 2024)
Noonan syndrome (NS) is a genetic disorder characterized by multiple congenital defects caused by mutations in the RAS/mitogen-activated protein kinase pathway. Male fertility has been reported to be impaired in NS, but only few studies have focused on fertility status in NS patients and underlying mechanisms are still incompletely understood. We describe a case of a 35-years-old man who underwent andrological evaluation due to erectile dysfunction and severe oligospermia. At clinical examination a syndromic facial appearance and reduced testis size were present. Hormonal evaluation showed normal total testosterone level, high FSH level and low-normal AMH and inhibin B, compatible with primary Sertoli cell dysfunction. Genetic analysis demonstrated the pathogenetic heterozygous variant c.742G > A, p.(Gly248Arg) of LZTR1 gene (NM_006767.3). This case report provides increased knowledge on primary gonadal dysfunction in men with NS and enriches the clinical spectrum of NS from a rare variant in the novel gene LZTR1.